Idiopathic collapsing glomerulopathy: A clinicopathologic analysis of 30 cases - Ahuja, A. (Medknow Publications & Media Pvt Ltd, 2014)
Collapsing glomerulopathy (CG) is a distinct clinicopathologic entity associated with various infections, medications and acute ischemia. There have been few scattered reports of CG from India. This study aimed at evaluating the clinicopathologic features of idiopathic CG in Indian patients with comparison between adult-onset and childhood CG. This study included all cases of idiopathic CG diagnosed over a period of 4 years (2006-2009). Appropriate clinical details and laboratory findings were retrieved. Renal biopsies were reviewed and detailed pathologic features assessed. Statistical analysis was performed to compare various features between adult-onset and childhood CG. Over these 4 years, 30 cases of idiopathic CG were diagnosed. Of these, 11 were children. Childhood CG cases had longer duration of symptoms and lower serum urea and creatinine levels compared with adult patients. In renal histology, tubular atrophy and interstitial fibrosis was frequent in our cases. Pediatric cases of CG showed a higher proportion of segmental glomerulosclerosis. On clinical follow-up, nine of the 30 patients progressed to end-stage renal disease and these included two pediatric patients. Idiopathic CG is a significant cause of renal dysfunction in both pediatric and adult patients. Childhood and adult-onset CG differ in few clinicopathologic features. Early and accurate diagnosis of CG is imperative for appropriate management of these patients.